Split Thickness Skin Grafts (STSG): Approach in necrotising fasciitis, a rare case report - Agung Widianto; Wahyu Kartiko Tomo (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Treatment of necrotising fasciitis including systemic antibiotic and radical surgical debridement is often resulting in large wounds that need to be closed using methods such as split-thickness skin grafts, local flaps, or guided tissue regeneration procedures. In this case report, 53 year-old male was diagnosed with necrotising fasciitis and treated surgically. The wound was treated initially with extensive debridement, wound treatment with platelet-rich plasma and finally closing the wound with split-thickness skin grafts. Split-thickness skin grafts can provide fast recovery and functional skin.